2003
DOI: 10.1038/emm.2003.5
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis-suppressor KAI1/CD82 induces homotypic aggregation of human prostate cancer cells through Src-dependent pathway

Abstract: To investigate the functional role of KAI1/CD82, a metastasis suppressor for human prostate cancer, in the regulation of homotypic cell adhesion, we transfected KAI1 cDNA into DU 145 human prostate cancer cells and established stable transfectant clones with high KAI1/CD82 expression. The KAI1 transfectant cells exhibited significantly increased homotypic cell aggregation in comparison with the control transfectant cells. This aggregation of the KAI1 transfectants was further enhanced upon exposure to anti-CD8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 1 publication
0
31
0
Order By: Relevance
“…Previous studies have suggested that CD82 may act positively to activate signaling to Src and FAK (Lagaudriere-Gesbert et al, 1998;Berditchevski and Odintsova, 1999;Jee et al, 2003). In T cells, anti-CD82 antibodies were shown to activate p56lck, a member of Src kinase family; however, this was only observed in the context of costimulation of the T-cell receptor and was not observed upon cell adhesion to anti-CD82 antibodies (Lagaudriere-Gesbert et al, 1998).…”
Section: Cd82 Regulates C-met Signaling Sc Sridhar and Ck Mirantimentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies have suggested that CD82 may act positively to activate signaling to Src and FAK (Lagaudriere-Gesbert et al, 1998;Berditchevski and Odintsova, 1999;Jee et al, 2003). In T cells, anti-CD82 antibodies were shown to activate p56lck, a member of Src kinase family; however, this was only observed in the context of costimulation of the T-cell receptor and was not observed upon cell adhesion to anti-CD82 antibodies (Lagaudriere-Gesbert et al, 1998).…”
Section: Cd82 Regulates C-met Signaling Sc Sridhar and Ck Mirantimentioning
confidence: 96%
“…In T cells, anti-CD82 antibodies were shown to activate p56lck, a member of Src kinase family; however, this was only observed in the context of costimulation of the T-cell receptor and was not observed upon cell adhesion to anti-CD82 antibodies (Lagaudriere-Gesbert et al, 1998). In CD82-transfected DU145 cells, anti-CD82 antibody enhanced Src kinase activity in cell-cell aggregates in suspension independently of integrins (Jee et al, 2003). However, these two examples do not address the same biological question; what is the role of CD82 in regulating integrin functions.…”
Section: Cd82 Regulates C-met Signaling Sc Sridhar and Ck Mirantimentioning
confidence: 98%
“…C-Src is largely involved in pathophysiology of osteoblasts (Marzia et al, 2000) and CD99 isoforms differently affect tumour metastasis K Scotlandi et al prostate cancer (Jee et al, 2003;Recchia et al, 2003) along with the significant role that it plays in the regulation of crucial processes implicated in the pathogenesis and progression of tumours, such as cell cycle, migration, resistance to anoikis and anchorage independence (Irby and Yeatman, 2000). Therefore, we evaluated its role as a possible mediator of CD99 functions.…”
Section: Differences In Migration and Metastasis Are Related To Cd99 mentioning
confidence: 99%
“…Within this context, KAI1/ CD82 is proposed to modulate signals controlling the interactions between cells, and between cells and their extracellular environment. Consistent with this function, and a role as a metastasis suppressor, the loss of KAI1/CD82 protein expression is associated with dramatically increased in vitro invasive and in vivo metastatic behaviour of tumour cells (4)(5)(6)(7). Although it is clear that these effects are associated with reduced interactions between cells, and altered interactions between cells and specific extra-cellular matrix components, the underlying basis for these changes is unknown.…”
Section: Introductionmentioning
confidence: 98%